Perceived Stress, Social Media Dependence, and Sleep Quality as Predictors of Information Resource Utilization among Undergraduate Students in Ibadan, Nigeria: The Moderating Role of Information-Seeking Behaviour - Obiyinka, Sunday Omoniyi; Araromi, Adedotun Aderele; Osobisi, David Oyedele (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026, 2026)
This study examined perceived stress, social media dependence, and sleep quality as predictors of information resource utilization among undergraduate students in Ibadan, Nigeria, with information-seeking behaviour as a moderating variable. The study adopted a descriptive survey research design. A sample of 176 undergraduate students was selected across universities in Ibadan using a multistage sampling procedure. Data were collected using standardized instruments, including the Perceived Stress Scale (PSS-10), Bergen Social Media Addiction Scale (BSMAS), Pittsburgh Sleep Quality Index (PSQI), an adapted Information-Seeking Behaviour Scale, and an Information Resource Utilization Scale. The data were analyzed using descriptive statistics, Pearson Product Moment Correlation, multiple regression, and hierarchical regression analysis at the 0.05 level of significance. The findings revealed that perceived stress, social media dependence, and sleep quality were significantly related to information resource utilization. The results further showed that the three independent variables jointly contributed significantly to information resource utilization, accounting for a substantial proportion of variance in the dependent variable. In terms of relative contribution, perceived stress emerged as the strongest predictor, followed by sleep quality and social media dependence. Additionally, information-seeking behaviour significantly moderated the relationship between the independent variables and information resource utilization, indicating that students with higher information-seeking competence were better able to utilize academic resources despite psychosocial challenges. The study concluded that psychological and behavioural factors play a critical role in shaping students’ use of academic information resources, and that information-seeking behaviour can buffer the negative effects of stress, social media dependence, and poor sleep quality. It was therefore recommended that universities should implement stress management programs, promote healthy digital habits, encourage good sleep practices, and strengthen information literacy training to enhance effective utilization of library resources among students. Keywords: Perceived stress, social media dependence, sleep quality, information resource utilization, information-seeking behaviour